2020
DOI: 10.1136/bmjopen-2019-033356
|View full text |Cite
|
Sign up to set email alerts
|

Impact evaluation of the free maternal healthcare policy on the risk of neonatal and infant deaths in four sub-Saharan African countries: a quasi-experimental design with propensity score Kernel matching and difference in differences analysis

Abstract: ObjectiveDespite the huge financial investment in the free maternal healthcare policy (FMHCP) by the Governments of Ghana and Burkina Faso, no study has quantified the impact of FMHCP on the relative reduction in neonatal and infant mortality rates using a more rigorous matching procedure with the difference in differences (DID) analysis. This study used several rounds of publicly available population-based complex survey data to determine the impact of FMHCP on neonatal and infant mortality rates in these two… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 11 publications
(14 citation statements)
references
References 25 publications
1
13
0
Order By: Relevance
“…To place this in context, recent quasi‐experimental evidence comparing Ghana and Burkina Faso against Nigeria and Zambia (Dwomoh et al, 2020) suggests that free maternal healthcare can cut the risk of infant mortality by more than half (RR = 0.46, 95%CI: 0.36 to 0.59). A recent randomised trial conducted in five districts of India reported smaller but still large magnitude reductions in odds of infant mortality (OR = 0.67, 95%CI: 0.54 to 0.83) for home‐based newborn care delivered by dedicated health workers (Rasaily et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…To place this in context, recent quasi‐experimental evidence comparing Ghana and Burkina Faso against Nigeria and Zambia (Dwomoh et al, 2020) suggests that free maternal healthcare can cut the risk of infant mortality by more than half (RR = 0.46, 95%CI: 0.36 to 0.59). A recent randomised trial conducted in five districts of India reported smaller but still large magnitude reductions in odds of infant mortality (OR = 0.67, 95%CI: 0.54 to 0.83) for home‐based newborn care delivered by dedicated health workers (Rasaily et al, 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Clustering and stratification will be adjusted for using sample survey weighting at all stages of the analysis. This will produce unbiased treatment estimate that can be generalized to the original survey population [ 26 , 52 ].…”
Section: Methodsmentioning
confidence: 99%
“…Within country policy interventions have ranged from equitable access to healthcare to the provision of quality healthcare at all levels for pregnant mothers and newborns [ 22 24 ]. In a similar vein, Ghana introduced one of such policies in 2008 dubbed, the ‘Free’ Maternal Healthcare Policy (FMHCP) with a primary aim of increasing facility delivery utilization and to achieve maternal and newborn care in general [ 3 , 25 , 26 ].…”
Section: Introductionmentioning
confidence: 99%
“…In line with the access to care policy, Ghana declared the ‘free’ registration of pregnant women as an exemption package of its national health insurance scheme (NHIS) in 2008 aimed at bridging the access gap to care to improve utilization of maternal health care services, thereby mitigating inequalities effect to enhance newborn care survival [ 19 , 20 ].…”
Section: Introductionmentioning
confidence: 99%